POTENTIAL AND FEASIBILITY OF DEVELOPMENT OF COCONUT PRODUCT HILIRATION IN INDRAGIRI HILIR REGENCY, RIAU PROVINCE - Shinta Utiya Syah (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
Indragiri Hilir has a coconut area of 351,526 Ha (BPS Riau, 2021). The coconut plantation commodity has become a development priority by placing it as a regional superior commodity. One of the efforts to increase the selling value of coconut products is in the context of increasing the acceptance of farmers or MSMEs in developing downstream products from coconut. The purpose of this activity is to calculate the potential and feasibility of developing downstream coconut products and developing technology for downstream coconut products. The area of smallholder coconut plantations in the identified Mandah sub-district is 35,304 ha spread over 17 villages with a production of 21,217.10 tons/year, Kuala Indragiri sub-district has been identified as covering an area of 36,673.79 ha, with a production of 19,943.6 tons/year, Kuala Enok is identified as an area of 38,244.73 ha with a production of 35,563.06 tons/year, Reteh District was identified with an area of 23,610.85 ha with a production of 25,405.18 tons/year. The superior products of coconut downstream in Indragiri Hilir Regency are coconut sugar (brown sugar), ant sugar, nata de coco, Virgin Coconut Oil (VCO), clear coconut oil while the feasibility of coconut downstream products that are feasible to develop for MSMEs in Indragiri Hilir district are MSMEs engaged in brown sugar, brown sugar and nata de coco products